Prevalence of autism spectrum disorders in adult psychiatric patients: a systematic review - Khaustova Олена; Marcenkovs’ka Інна (Psychosomatic Medicine and General Practice, 2019)
Taking into account the prevalence of autism spectrum disorders (ASD) among adults, there is not enough data on the prevalence of ASD among persons undergoing in-patient psychiatric treatment. The purpose of this review is to conduct a systematic review of the literature on the prevalence of autistic spectrum disorders among adult psychiatric inpatients. The criteria for incorporating the articles included: a) the study of the prevalence of autism spectrum disorders; b) research in the population of adult psychiatric inpatient institutions. The review of the articles was carried out in the following electronic databases: PubMed, Medline, CINAHL, PsycINFO and EMBASE. Also, to expand the volume of data, the consultations of specialists in this field were used. As a result of the search, four studies were identified that met the criteria for inclusion in different psychiatric inpatient settings, including private and public. There were significant differences in methodological approaches, including screening tests, diagnostic tools, used diagnostic criteria. Estimates of the prevalence of ASD among the adult population in the psychiatric hospital ranged from 1.7 to 9.6%. From currently available data from a number of studies, it has been found that the prevalence of ASD increases in inpatient psychiatric conditions relative to the general population. There is a need for further research among this group of patients to expand the evidence base, as well as to develop effective strategies for identifying patients with a high probability of ASD in psychiatric inpatient settings among the adult population. Adult patients who are in psychiatric hospitals can indeed become a target for identifying those who have ASD, although it must first be determined that ASD is indeed a significantly more common disorder among people in this group relative to the community.